Interaction Between Receptor TIR1 and Auxin Plant Hormone in Arabidopsis thaliana - Sari, Annisa N; Nindyawati, Dwi L; Aqmarina, Ananda; Widhiya, Eva W; Lestari, N D (Bioinformatics and Biomedical Research Journal, 2018)
Auxins in gene transcription have influence that primarily mediated by TIR1 receptors, which can change the conformation of receptors and thereby promotes their interaction with auxin proteins. Recent research findings provide an increased understanding of the auxins that usually used in Arabidopsis thaliana was IAA and IBA in plant culture. The objectives of this to know the most potential auxin for inducing TIR1 receptor. Ligand (IAA, IBA, 2,4D, IPA, NAA, and Indole acetamid) and receptor (TIR1) collected from PDB, structure visualization using Pymol[10], docking between them using PyRx, and analysis of the interation using LigPlot+. Each ligand dock with receptor TIR1 in the same binding site. Docking result show IAA and IBA have highets binding affinity than other ligands. Binding analysis result show each ligand bind with different amino acid on receptor TIR1. 2,4D bind with Ser438; IAA with Leu439, Ser438, and Arg403; IBA with Leu439, Ser462, Arg436, and Arg403; Indole acetamid with Leu439, Ser438, and Arg403; IPA Leu439, Arg403, and Ser438; also NAA with Leu439. Keywords: Auxins, docking, in silico, TIR1